The Influence of Environmental Factors on Performance in Table Tennis: A Literature Study - Mawardinur; Bp, Amanda Karunia Puteri; Bangun, Berby Yoreza br.; Lubis, Khoiruddin; Al Farizi , Salman (Journal Coaching Education Sports, 2024)
This study aims to explore the influence of environmental factors such as lighting, temperature, humidity, noise, and table surface type on performance in table tennis. A literature review method was used to analyze findings from various relevant studies in this field. The results of the review indicate that environmental factors play a significant role in affecting concentration, physical and mental performance, as well as players' game control in table tennis. Low lighting, extreme temperatures, high humidity, environmental noise, and table surface type are significant variables in influencing player performance. The implications of this research underscore the importance of understanding and adapting to environmental factors for table tennis players to enhance their performance and achievements in this sport. Further research is recommended to delve deeper into the interaction between environmental factors and performance in table tennis.